Unlocking Scholarly Access Beyond Boundaries: Strategies, Lessons, and Challenges in Implementing an Institutional Repository at Quaid I Azam University Library, Pakistan - Mirza, Khalid Bashir; Arif, Muhammad; Ullah, Midrar; Hamid, Muhammad (The International information & library review, 2024)
Libraries, particularly academic libraries globally, have begun to recognize the significance of digitally preserving their Indigenous scholarly outputs. They are also more actively involved in digitization, digital preservation, and the establishment of their Institutional Repositories (IRs). In Pakistan, academic libraries have significantly transformed their methods of managing indigenous scholarly literature, particularly theses and dissertations (TDs), aligning with global practices. The recent emergence of institution-based repositories for archiving research work is gaining acceptance from academic institutions in the country. This article outlines the experience of establishing an IR designated as Quaid I Azam University Research Repository (QAU RR) to preserve research outputs at this premier federal university in Pakistan. It provides a concise account of the processes, steps, and strategies adopted in the implementation of an RR project aimed at digitally preserving a collection of research projects, TDs. The study leverages practical experience, expertise, and knowledge gained through the establishment of an e-theses repository deploying DSpace software. QAU library employed a cost-effective strategy for digitizing and digitally preserving its entire print TDs collection without incurring any additional financial grants, hardware, or human resources. This repository is expected to be beneficial not only for local researchers, scholars, and faculty members engaged in teaching, research, and scholarly activities but also aims to serve the broader global community. QAU repository holds a substantial collection of 27,014 Electronic Theses and Dissertations (ETDs). The knowledge and outcome of this study are valuable for institutions, particularly in developing countries, intending to develop their IRs.